Assessment of Wound Healing Activity of the Aqueous Extracts of Colutea cilicica Boiss. & Bal. Fruits and Leaves. (14th February 2011) - Peşin Süntar, Ipek; Koca, Ufuk; Küpeli Akkol, Esra; Yılmazer, Demet; Alper, Murat
Abstract : The fruiting branches of Colutea cilicica Boiss. & Bal., along with leaves and fruits, have been used to heal inflammatory wounds at traditional medicine in various parts of Turkey. In order to evaluate the wound healing activity of the plant, aqueous extracts were prepared from the flowering parts and fruits of Colutea cilicica Boiss. & Bal. by using 40 ° C distilled water. Incision wound healing models by using tensiometer on rats and excision wound healing models on mice were employed to assess the activity. Significant wound healing activity was observed when ointment formulation of the aqueous extract at 1% concentration was applied on the mentioned models. The fruit extract treated the groups of animals, showing a 78.1% contraction in wounds, which was close to the contraction value of the reference drug Madecassol (100%). On the other hand, the same extract used on the incision wound model demonstrated a significant increase (42%) in wound tensile strength, compared to the flowering aerial parts. Histopathological examination also supported the results shown in both the incision and excision wound models. The wound healing effect was evaluated and compared with the reference ointment Madecassol. Moreover, zinc and vitamin C levels in the fruit (9480 ± 0 mcg g −1 ; 389 mg g −1 ) and flowering aerial part (6609 ± 1 mcg g −1 ; 404 mg g −1 ) extracts, which might have contributed to the wound healing process, were determined. The experimental data confirmed the traditional usage of C. cilicica Bois s. & Bal.